1983
DOI: 10.2105/ajph.73.5.500
|View full text |Cite
|
Sign up to set email alerts
|

The rural dental health program: the effect of a school-based, dental health education program on children's utilization of dental services.

Abstract: Eighteen-hundred rural children ages five through thirteen were randomly assigned for dental treatment to a school-based practice, and to private practitioners in the community. Simultaneously, five of the nine public schools attended by the children offered an enriched program of dental education while the remaining schools taught the regular health education courses. All children participated in a school based fluoride program and their dental treatment was provided without charge.Data indicating how the chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…This study, which ran from 1975 to 1979, found that a school-based dental education program encouraged greater use of preventive dental services in a population of primary school children. However, even though their preventive behavior changed, these children experience comparable increments of decayed teeth as those in schools providing the regular, state-mandated health programs (Bentley, Cormier and Oler, 1983). Similar findings were reported from the National Preventive Dentistry Demonstration Program (Klein, Bohannan, Bell, Disney, Foch & Gravee, 1985).…”
supporting
confidence: 65%
See 2 more Smart Citations
“…This study, which ran from 1975 to 1979, found that a school-based dental education program encouraged greater use of preventive dental services in a population of primary school children. However, even though their preventive behavior changed, these children experience comparable increments of decayed teeth as those in schools providing the regular, state-mandated health programs (Bentley, Cormier and Oler, 1983). Similar findings were reported from the National Preventive Dentistry Demonstration Program (Klein, Bohannan, Bell, Disney, Foch & Gravee, 1985).…”
supporting
confidence: 65%
“…Participating students were screened annually by outside examiners who recorded the number of decayed surfaces, the level of plaque, and the gingival and orthodontic status of each child in the study. A more complete description of the study design used in the original study has been published (Bentley, Cormier & Oler, 1983;Bentley, Green & Ship, 1984). This section describes the methods used in a follow-up study of children who participated in the Rural Dental Health Program.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our scoping review results, we identified three categories of programs that have been implemented in various universities. The first category characterizes programs for the training and education of dental and allied health students and professionals [1, 3, 11, 24–67]; the second category describes programs for the education and training of rural and remote community members [68–73] and the third category represents programs on oral healthcare services in rural and remote areas [41, 42, 61–63, 68, 69, 73–92].…”
Section: Program Classificationmentioning
confidence: 99%
“…These programs included 1 to 10 weeks of rural placement training for dental students (mostly fourth and fifth years and internship level) and dental hygiene students; dental education courses; outreach programs; postgraduate fellowship programs; and programs to encourage rural students, under-represented minority and low-income students to study and practice dentistry. The platform for the second category of education and training programs for rural and remote community members included patient oral health education and rural school teachers’ training [6871]. Lastly, the curriculum based platform for programs in the third category of oral health care services incorporated programs for providing and improving oral health care services and fulfilling the community’s oral health-related needs [41, 42, 61, 62, 68, 69, 7479].…”
Section: Program Classificationmentioning
confidence: 99%